2017
DOI: 10.3329/bjsr.v29i2.32333
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield performance of selected wheat varieties under water deficit conditions

Abstract: Effect of water deficit stress on growth and yield of three wheat (Triticum aestivum) varieties, viz. BARI Gom 25, BARI Gom 26 and Sourav was studied. Water deficit lowered the light interception at anthesis in wheat. Under water deficit condition, the highest amount of PAR interception was recorded in BARI Gom 26. The reduction of leaf area index (LAI), crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) were less in BARI Gom 26. Water deficit conditions lowered the SPAD values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…In the maturation period, 9.36 g of day -1 ve and 7.62 g of day -1 are reduced to -9.84 g of day -1 in the ripening period (R 2 = 0.7912). Similar decreases were reported by Spitters and Kramer (1986) and Zaman et al (2016) by decreasing leaf area and decreasing photosynthesis capacity due to aging.…”
Section: Resultssupporting
confidence: 86%
“…In the maturation period, 9.36 g of day -1 ve and 7.62 g of day -1 are reduced to -9.84 g of day -1 in the ripening period (R 2 = 0.7912). Similar decreases were reported by Spitters and Kramer (1986) and Zaman et al (2016) by decreasing leaf area and decreasing photosynthesis capacity due to aging.…”
Section: Resultssupporting
confidence: 86%
“…Maximum CGR and LAI were also obtained with wheat variety Raj 4037. Zaman et al (2016) also reported that dry matter accumulation, crop growth rate and leaf area index were significantly influenced by different wheat varieties. Highest chlorophyll content in leaves was obtained in variety Raj 4037.…”
Section: Resultsmentioning
confidence: 96%
“…Two general approaches to the derivation of LAIs are now apparent in the literature. The first uses actual measurements of leaf area (e.g., Camargo et al., ; Odum, Copeland, & Brown, ; Njuguna, Kamiri, Okalebo, Ngetich, & Kebeney, ; Zaman, Karim, Bari, Akter, & Ahmed, ). The second, of more recent origin, uses proxy measurements, such as light‐sensing, hand‐held scanners or remote‐sensing satellites (e.g., Clevers, Kooistra, & van den Brande, ; Kim et al., ; Verger, Filella, Baret, & Peñuelas, ).…”
Section: Introductionmentioning
confidence: 99%